Biomass stemmed activated carbon electrodes toward a significant electric double-layer capacitor - Abhimanyu Singh; Gaurav Nath; Pawan Singh Dhapola; Sushant Kumar; Tejas Sharma; Yee Hang Soo; H. K. Jun; Pramod K. Singh; Sunanda Kakroo; Aalia Farid; Marium Khan; Serguei V. Savilov; et al. (Materials for Renewable and Sustainable Energy, 2023)
Abstract The primary goal of the current study is to improve the specific capacitance of electric double-layer (EDLC) device using biomass (Tribulus Terrestris) derived activated carbon electrodes synthesized by chemical activation method. Furthermore, high surface area carbon electrodes are characterized using X-ray diffraction (XRD), RAMAN spectroscopy, and scanning electron microscopy (SEM) to confirm the morphological structure. Finally, the electrochemical performance of fabricated EDLC proves a good agreement data using Cyclic Voltammetry (CV), Low Impedance Spectroscopy (LIS), and Galvanostatic Charge–Discharge (GCD) analysis showing the high specific capacitance of 115 Fg−1 for the optimized 1:2 activated carbon material.